The Analysis of Borneo FC 1st Indonesian League Football Player Body Composition - Sudari, Sudari; Siswanto, Hendro; Pamungkas, Hari; Yusus, Havid; Nidomuddin, Muhammad (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
Proper body composition is an important role in sports performance that is not optimal can reduce the athlete's physical fitness so that the performance decrease when competition occur. Professional soccer players often work closely with a team of coaches, nutritionists and medical professionals who can help them plan the right nutrition and training strategies suitable for the Borneo FC team, the participants in Indonesia's highest league caste. The average body fat of 12.4% is in the very good category, the BMR with an average of 1636 kcal belongs to the normal category, the free fat mass index (FFMI) averages 61 in the good category and the total body water (TBW) with an average of 65% is included in the normal category. The body composition of Borneo FC soccer players can be stated that 67.8% body fat is in the very good category, 85.7% body metabolism rate (bmr) is normal, 42.8% free fat mass index is good and total body water is 100% normal. These results can be used as a reference in determining the nutrition and nutrition program for each player so that the condition of the body composition of the players can be maintained and balanced.